Pengaruh Variasi Penambahan Limbah Plastik Terhadap Kekuatan Tekan Batako Dalam Upaya Pemanfaatan Limbah - Kusdiyono Kusdiyono; Supriyadi Supriyadi; Mochammad Tri Rochadi; Herry Ludiro Wahyono (Politeknik Negeri Semarang, 2018)
At this time, plastic is a material that is needed by the public at large and the impactis also extraordinary after the plastic is used in daily life which can cause seriousproblems if the management is not done properly. The problem of plastic waste doesnot only occur in the city of Semarang, but also in other cities, so the Ministry ofEnvironment and Forestry has implemented a pay-for-use plastic bag program inthe short term. But this is only to deal with problems in the short term. In the longterm, it will not solve the problem of